The effect of irradiance on the carbon balance and tissue characteristics of five herbaceous species differing in shade-tolerance - Pons, Thijs L.; Poorter, Hendrik (Frontiers in Plant Science, 2014)
Plant photosynthesis scales positively with growth irradiance. The carbon balance, defined here as the daily whole-plant gross CO2 assimilation (A) partitioned in C available for growth and C required for respiration (R), is thus irradiance dependent. Here we ask if R as a fraction of A is also irradiance dependent, whether there are systematic differences in C-balance between shade-tolerant and shade-intolerant species, and what the causes could be. Growth, gas exchange, chemical composition and leaf structure were analyzed for two shade-tolerant and three shade-intolerant herbaceous species that were hydroponically grown in a growth room at five irradiances from 20 µmol m-2 s-1 (1.2 mol m-2 day-1) to 500 µmol m-2 s-1 (30 mol m-2 day-1). Growth analysis showed little difference between species in unit leaf rate (dry mass increase per unit leaf area) at low irradiance, but lower rates for the shade-tolerant species at high irradiance, mainly as a result of their lower light saturated rate of photosynthesis. This resulted in lower relative growth rates in these conditions. Daily whole-plant R scaled with A in a very tight manner, giving a remarkably constant R/A ratio of around 0.3 for all but the lowest irradiance. Although some shade-intolerant species showed tendencies towards a higher R/A and inefficiencies in terms of carbon and nitrogen investment in their leaves, no conclusive evidence was found for systematic differences in C-balance between the shade-tolerant and intolerant species at the lowest irradiance. Leaf tissue of the shade-tolerant species was characterized by high dry matter percentages, C-concentration and construction costs, which could be associated with a better defense in shade environments where leaf longevity matters. We conclude that shade-intolerant species have a competitive advantage at high irradiance due to superior potential growth rates, but that shade-tolerance is not necessarily associated with a superior C-balance at low irradian